KEKERASAN TERHADAP ISTRI DAN IDEOLOGI KELUARGA - , Gayatri Dyah Suprobowati (Fakultas Hukum Universitas Sebelas Maret, 2014)
Abstract This research aims to identify how women in this case the wife get experience in reality when the conflict with the law. Methods to be used is a qualitative research method with the data taken from the observation, interviews and focus group discussions with the Implementation of the victims of domestic violence. As a conclusion, need to follow the proper steps to eliminate discrimination against women in all matters relating to marriage and family relations on the basis of equality between man and women . Keywords : violence, wife, ideology of family.